Early Adolescent Sub-Chronic Low Dose Nicotine Exposure Increases Subsequent Cocaine and Fentanyl Self-Administration in Sprague Dawley Rats - CARDENAS, Anjelica (Behav Pharmacol, 2021)
An exponential rise in nicotine-containing electronic-cigarette use has been observed during the period of adolescence. Preclinical studies have shown that nicotine exposure during early adolescence, but not adulthood, increases subsequent drug intake and reward. Although growing clinical trends highlight that stimulant use disorders are associated with the opioid epidemic, very few studies have assessed the effects of adolescent nicotine exposure on opioid intake. The objective of our current study is to develop a new animal model to assess the causal relationship of adolescent nicotine exposure on subsequent opioid intake. In this effort, we first replicate previous studies using a well-established 4-day nicotine paradigm. Rats are pretreated with a low dose of nicotine (2x, 30 μg/kg/0.1 mL, i.v.) or saline during early adolescence (PN 28–31) or adulthood (PN 86–89). Following nicotine pretreatment on PN 32 or PN 90, animals underwent operant intravenous self-administration for the psychostimulant, cocaine (500 μg/kg/infusion (inf)) or the opioid, fentanyl (2.5 μg/kg/inf). We successfully show that adolescent, but not adult, nicotine exposure enhances cocaine self-administration in male rats. Furthermore, we illustrate early adolescent, but not adult nicotine exposure enhances fentanyl self-administration, independent of sex. Overall, our findings highlight that adolescence is a unique period of development that is vulnerable to nicotine-induced enhancement for cocaine and fentanyl self-administration in rats.